A Survey on Design and Implementation of Mimo Antennas for Wireless Communication - Bodepudi, Hanish Chaitanya; Raaza, Arun; Rajendran, V.; Prabhu, V.; Meena, M. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This multiple-input multiple- output (MIMO) communication has shown to be an effective method for enhancing the performance and capacity of wireless communications systems. The MIMO antenna is highly important in the world of wireless networking today. Over the past 10 years, the field of MIMO antennas has seen a significant amount of study. A new area of connection between vehicles and the infrastructure at the side of the road is called vehicular communication. The opportunity for the distribution of information across real-time communication between vehicles and related infrastructure is being created by advancements in wireless communications. High data rate innovative in-vehicle wireless communications may be achieved with Ultra-Wide Band (UWB) technology. Ultra-wideband (UWB) and multiband antennas are being inflated in analysis due to semiconductor units pursuit of high data speeds. Keyless entry, safety, free of driving, Digital keys, vehicle recovery, and vehicle-to-vehicle communication from a blocked parking space are just a few of the automotive uses for UWB antenna units (Internet of Things). The many uses for multiple-input multiple-output (MIMO) antennas are covered in this survey article. Here the UWB (Ultra Wide Band) MIMO antennas for automotive communication are discussed and their result analysis is discussed.